High prevalence of malnutrition and deranged relationship between energy demands and food intake in advanced non‐small cell lung cancer. (21st April 2016) - Mohan, A.; Poulose, R.; Kulshreshtha, I.; Chautani, A.M.; Madan, K.; Hadda, V.; Guleria, R.
Abstract : The relation between dietary intake and metabolic profile in non‐small cell lung cancer (NSCLC) was evaluated. Patients with NSCLC were recruited and their caloric requirement and resting energy expenditure (REE) were calculated using the Harris–Benedict equation and Katch–McArdle formula respectively. Hypermetabolic state was defined as REE more than 10% above the basal metabolic rate (BMR). Body composition parameters were calculated by bioelectric impedance method. The 24‐h dietary intake method and Malnutrition Universal Screening Tool assessed nutritional intake. One hundred and forty‐eight subjects were included (87% males). Of these, 46.6% subjects were hypermetabolic and 31% cachexic, with lower calorie and protein intakes than recommended, although per cent of total energy derived from protein, fat and carbohydrates were similar. Hypermetabolic patients had lower BMI, though the per cent deficit in energy and protein consumption was similar. Cachexia was associated with lower BMR but not with deficit in energy or protein consumption. No correlation was seen between dietary intake and body composition parameters. The calorie and protein intake of NSCLC patients is lower than recommended. The discordance between elevated REE and dietary intake implies that the relationship between increased energy demands and food intake may be altered.